2018
DOI: 10.30699/mmlj17-01-03
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Isolates of Acinetobacter baumannii isolated from Tehran Hospitals Using ERIC-PCR Method

Abstract: Background and Objective:Acinetobacter is a genus of non-fermenting Gram-negative cocci or coccobacilli, which have low nutritional requirements for growth and can survive for a long time in adverse conditions, on dry surfaces, and also in aqueous environments. The importance of the members of Acinetobacter genus as pathogens involved in nosocomial infections, is increasing. Acinetobacter baumannii is the most common species involved in a broad spectrum of nosocomial infections, including pneumonia, bacteremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Further, cluster II contained isolates from the other Puzi River area (p-value = 90%) ( Figure 3). Maleki et al (2016) found that the diversity of genetic patterns of A. baumannii that were observed by ERIC-PCR analysis was due to the wide distribution in hospitals [2]. Here, we postulate that this high diversity is due to the distributions of sampling sites with different sources.…”
Section: Eric-pcr Fingerprint Analysismentioning
confidence: 59%
See 4 more Smart Citations
“…Further, cluster II contained isolates from the other Puzi River area (p-value = 90%) ( Figure 3). Maleki et al (2016) found that the diversity of genetic patterns of A. baumannii that were observed by ERIC-PCR analysis was due to the wide distribution in hospitals [2]. Here, we postulate that this high diversity is due to the distributions of sampling sites with different sources.…”
Section: Eric-pcr Fingerprint Analysismentioning
confidence: 59%
“…Molecular genotyping methods, including plasmid profiling, ribotyping, PFGE, MLST, and PCR-based typing methods, have been evaluated as potential methods to characterise A. baumannii isolates [6]. Despite MLST and PFGE being highly discriminative genotyping methods, PCR-based DNA fingerprinting techniques have advantages of performance ease and economic viability [2,6,12]. To date, there have been many studies describing different PCR-based methods to type MDR-AB [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations